Comparison of the Effectiveness of Time Management Training, Motivational Strategies, and Self-Regulated Learning Strategies Training on Female Senior Elementary School Students’ Academic Self-Concept - Zahra Salmani; Ali Mehdad; Mohammad Ali Nadi Khorasgan (مطالعات روانشناسی تربیتی, 2024)
The aim of present study was to compare effectiveness of time management training, motivational strategy and self-regulation strategy packages on academic self-concept in students with exam anxiety among second year of elementary school. Research method was quasi-experimental with pre-test-post-test design and two-month follow-up period. statistical population included all students with exam anxiety in academic year 2022-2023 in second term of Chadegan elementary school, after the implementation of exam anxiety questionnaire by Abolghasemi et al (1997)., 72 students were purposefully selected and randomly assigned in 3 experimental groups and 1 control group, each including 18 students. For experimental groups, time management by Brian Tracy (2008) and motivational strategy training by Nazemy, et al. (2020) was carried out for 8 sessions of 60 minutes each and self-regulation by Dansereau et al (1979) for 8 sessions of 90 minutes, and control group did not receive any intervention. Then, all groups answered Chen and Thompson (2004) Academic self-concept Scale in three phases: pre-test, post-test and follow-up. Data analysis was performed using ANOVA with repeated measures. The results showed that time management training, motivational strategies, and self-regulated learning strategies was effective on increasing academic self concept) p<0/05), and according to the Bonferroni test, no significant difference was observed between the effectiveness of the packages (p>0/05). According to the results of the research, it is suggested to the policymakers of the education system that the use of these three educational packages to increase the academic self-concept of students should be placed in the educational priorities.